Microemulsions: An Encapsulation Strategy to Increase the Thermal Stability of D-limonene - Bruna Rodrigues Belem; Gustavo Vaiano Carapeto; Michele Georges Issa; Humberto Gomes Ferraz (MDPI AG, 2023)
D-limonene, derived from citrus essential oils, holds significant therapeutic potential but faces challenges due to its high volatility, especially in pharmaceutical formulations. This study investigates microemulsions as a promising delivery system for volatile compounds, emphasizing their thermal protection for D-limonene. The formulation development was guided by a pseudo-ternary phase diagram and involved assays with different surfactants. Microemulsions were achieved solely with Labrasol® (Gattefossé Brasil, São Paulo, Brazil), encompassing concentrations of 7.1% to 30.8% D-limonene, 28.6% to 57.1% Labrasol®, and 20.0% to 64.3% water. All formulations were homogeneous, transparent, and presented low viscosity, with adequate D-limonene content, indicating that the production is feasible at room temperature. While the formulations demonstrated robust physical stability under mechanical stress, they exhibited destabilization at temperatures exceeding 50 °C. In terms of oxidative stability, pure D-limonene exhibited an induction period of 4.88 min, whereas microemulsions extended this period by four to eight times. Notably, the induction period of the microemulsions remained practically unchanged pre and post-heating (70 °C), suggesting the formulation's ability to enhance the D-limonene thermal stability. This highlights the value of oxidative stability analysis as a quicker tool than conventional oxidative tests, while affirming microemulsions as a viable encapsulation strategy for D-limonene protection against elevated temperatures.